1968
DOI: 10.1126/science.162.3852.475
|View full text |Cite
|
Sign up to set email alerts
|

Functional Asymmetry of the Human Brain

Abstract: Verbal and nonverbal memorization skills were tested before and after electroconvulsive shocks to the left, right, or both cerebral hemispheres of neurologically normal patients. As predicted, decrements for the left-hemisphere-shocked group were larger on the verbal than nonverbal tasks, while the reverse was true for the right-hemisphere-shocked group. Largest decrements on both tasks were shown by the bilaterally shocked group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0

Year Published

1970
1970
1983
1983

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(19 citation statements)
references
References 8 publications
1
18
0
Order By: Relevance
“…More persistent deficits in verbal memory, detected at least an hour after treatment, have also been reported (Cohen et al, 1968;Halliday et al, 1968;Cronin et al, 1970;D'Elia, 1970;Fleminger et ai., 1970). Neurological defects in the post-ictal period after non-dominant hemisphere 1135 ECT do not appear to have been shown but nonverbal/spatial deficits have been reported hours or days after treatment (Cohen et al, 1968;Halliday et al, 1968).…”
mentioning
confidence: 78%
See 1 more Smart Citation
“…More persistent deficits in verbal memory, detected at least an hour after treatment, have also been reported (Cohen et al, 1968;Halliday et al, 1968;Cronin et al, 1970;D'Elia, 1970;Fleminger et ai., 1970). Neurological defects in the post-ictal period after non-dominant hemisphere 1135 ECT do not appear to have been shown but nonverbal/spatial deficits have been reported hours or days after treatment (Cohen et al, 1968;Halliday et al, 1968).…”
mentioning
confidence: 78%
“…Several studies have shown that in the immediate post-ictal period after ECT to the dominant hemisphere, patients have signs of dysphasia which usually resolve within 30 minutes of treatment (Gottlieb and Wilson, 1965;Pratt et al, 1971;Clyma, 1975). More persistent deficits in verbal memory, detected at least an hour after treatment, have also been reported (Cohen et al, 1968;Halliday et al, 1968;Cronin et al, 1970;D'Elia, 1970;Fleminger et ai., 1970). Neurological defects in the post-ictal period after non-dominant hemisphere 1135 ECT do not appear to have been shown but nonverbal/spatial deficits have been reported hours or days after treatment (Cohen et al, 1968;Halliday et al, 1968).…”
mentioning
confidence: 99%
“…A prevalent dominance in verbal functions, and possibly in verbal memory, of the dominant hemisphere, and in nonverbal visuo-spatial tasks of the non-dominant hemisphere, is commonly assumed. Data obtained for patients with unilateral cerebral damage (Ki- mura 1963, De Kenzi & Spinnler 1966, see also Brierly 1966, Whitty & Lishmarz 1966, in cases unilaterally operated in the temporal lobe (Meyer 1959, Milner 1966 and in neurologically normal patients treated with NDand D-ECT (Cohen et al 1968) give support to this view. In our study, the decrement i l l the 30-Word-Pair Test was qignificantly lower in the ND-ECT-group than in D-and BI-ECT.…”
Section: Comments On the Resultsmentioning
confidence: 90%
“…Processing of verbal and nonverbal information can take place in different cortical hemispheres (Cohen, Noblin, Silverman, & Penick, 1968). Perhaps Ss can process information simultaneously by responding to different stimulus inputs with separate parts of the brain.…”
Section: Resultsmentioning
confidence: 99%